Modern antiseptics against multidrug-resistant Pseudomonas aeruginosa, emerging from war-related injuries in Ukraine - Nazarchuk, Oleksandr; Riesbeck, Kristian; Kovalchuk, Valentyn; Denysko, Tetiana; Faustova, Mariia; Chornopyshchuk, Roman; Nazarchuk, Halyna; Parkhomenko, Oleg; Bahniuk, Nataliia; Dmytriiev, Dmytro; Nagaichuk, Vasyl (Frontiers in Microbiology, 2025)
Susceptibility testing of clinical multidrug-resistant (MDR) and reference P. aeruginosa strains was performed using the standard twofold serial dilution method. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of antiseptics were determined. MIC and MBC values were also interpreted as the bacteriostatic index of antiseptic activity (BSIAA) and the bactericidal index of antiseptic activity (BCIAA). The ability of strains to form biofilms, the inhibition of biofilm formation, and the destruction of mature biofilms under the influence of bacteriostatic, bactericidal, and ½ of the initial antiseptic concentration were modeled using Christensen’s test. Antiseptics from the detergent group, decamethoxine (0.1 and 0.02%) and polyhexanide (0.1%), demonstrated the highest antimicrobial activity. Their bacteriostatic concentrations were 63.2 ± 5.2 μg/mL and 68.7 ± 4.2 μg/mL, respectively. The ranking of antiseptics by bacteriostatic efficacy was: decamethoxine > polyhexanide > octenidine > miramistin > chlorhexidine. The highest BSIAA values were observed for povidone-iodine 10%, decamethoxine 0.1%, octenidine 0.1%, and polyhexanide 0.1%. The highest bactericidal IAA values were found for povidone-iodine 10%, decamethoxine 0.1%, octenidine 0.1%, and polyhexanide 0.1%. Miramistin 0.01% was deemed insufficiently effective. Polyhexanide exhibited the highest bactericidal activity, with a BCIAA to BSIAA ratio of 0.88. For all other antiseptics, this ratio ranged from 0.5 to 0.6. All tested strains exhibited a high capacity for biofilm formation. All antiseptics significantly inhibited biofilm formation. Octenidine had the strongest effect on immature biofilms, reducing their formation by 28.5% (p < 0.0001). The MICs of most antiseptics stimulated mature biofilm development. The bacteriostatic concentration of octenidine led to the eradication of biofilm by 4.7% (p < 0.001) compared to the control. The MBC of most antiseptics (except chlorhexidine) eradicated mature biofilms by 4–30.6%, whereas chlorhexidine stimulated mature biofilm growth by 17.9%. All antiseptics, at half their initial concentration, partially eradicated MDR Pseudomonas biofilms by 11.3–42.4%. Analysing the effect of octenidine at different concentrations and stages of biofilm formation highlights its strong activity against P. aeruginosa biofilms. Our findings underscore the importance of carefully monitoring P. aeruginosa isolates for antiseptic susceptibility. This approach can help prevent the development of selective conditions that promote resistant microorganisms and limit their spread.